Hubungan Adversity Quotient dan Self Efficacy dengan Kreativitas Siswa di MA Mambaul Ulum Bata-Bata Pamekasan - Faruk, Umarul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to explain the relationship between adversity quotient and self-efficacy with creativity involving 80 students of Madrasah Aliyah Mambaul Ulum Bata-bata in Pamekasan (40 students of class X and 40 students of class XI). The measuring tools used are the adversity quotient scale and the creativity scale proposed by experts, as well as the self efficacy scale. The results showed that adversity quotient and self efficacy were significantly correlated with creativity where the value of F = 31.560 at the value of p = 0.000 (p < 0.01). The determination coefficient is 0.450, so this means that the adversity quotient variable and the self efficacy variable (independent variable) give an effective contribution together of 45% to the creativity variable (bound variable), while the remaining 55% is influenced by other variables that are not included in this study.